Relasi Kuasa Bisnis Daring Menghadapi Hegemoni Pasar Modern di Indonesia - Vibriza Juliswara (Universitas Trunojoyo Madura, 2019)
The hegemony was built in the understanding of the modern market trying to continue to enter into dictating the taste of the community, building the moral habits of its visitors. Ranging from fashion, food, as if the mall is something that has legitimacy to create parameters such as what lifestyle should be the current society. Along with social changes in society, now emerging online businesses as the most practical and ideal consumption medium. The online business is a medium of power relations, because meaningfully the internet is also a sign of high technology which cones social classes and social symbols. The development of online business in Indonesia is considered to be a solution in improving the economy of the lower classes. Because through online business, people can get the same access in marketing their products different from modern markets that tend to be exclusive. The impact of the emergence of online business in recent years for some people is considered a threat to the modern market. For modern markets that do not compete at low prices but compete with the uniqueness that is owned like creative shops, online business is not a threat.